ORIENTALIS DAN DUPLIKASI BAHASA ALQURAN (Telaah dan Sanggahan atas Karya Christoph Luxenberg) - Yusuf, Khaeruddin (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: The Qurâan is a holy book seving as the source of inspiration for the seekers of science, including those who belong to orientalists. They make Alquran as an object of study and research among both academic and non-academic. One of the most contemporary issues of orientalist studies of the Qurâan was written by Christoph Luxenberg âDie Syiro-aramaeische Lesart des Koran: Ein beitrag Zur Entschluesselung der KoranspracheâÂ  (The Syiro-Aramaic Reading of the Qurâan: A contribution to the Language of the Qurâan Description). Luxenberg says that the Qurâan is heavily influenced by the Syriac-Aramaic language; therefore, to understand the Quran properly, one must learn it through the Syriac-Aramaic language. According to Luxenberg, the Syriac-Aramaic language was the language of Lingua Franca of Arabic society at the time of the Prophet, while the Arabic language (Fusha) came later after the Syriac-Aramaic language had reached perfection. This article tries to review the opinion of Luxenberg, then gives arguments by citing the opinion of some prominent Islamic reviewers.Kata Kunci: Orientalis, otentitasÂ  Alquran, bahasa Alquran, Christoph Luxenberg